Ṭarā’iq Ta‘līm al-Qirā’ah wa-al-Kitābah wa-al-Rabṭ baynahumā li-Aṭfāl al-Marḥalah al-Asāsīyah min al-Ta‘alīm - Ghasaan 'Abd al-Majid (Al-Ma‘rifah, 2018)
This paper aims at clarifying some of the specificities of Arabic language teaching as well as shedding light on the learning difficulties faced by some trainees at the level of learning and learning skills. In the same context, this paper proposes new methodologies that help overcome some learning difficulties to achieve success at the primary level, and explain the relationship between reading and writing and linking these two skills. We have reached the following conclusions: To recognize the function of the teacher in the ability to connect between the processes of reading and writing, and to communicate the learner to the fact that reading is an interactive structural analysis, not intended to just know the words written and spoken correctly, but beyond to understand what he reads between his knowledge and experience And to interpret the reading material and do it using the ability to imagine and think and then try to formulate all this and use in the writing process.